The Effect of Sign Language on the Language Development of Deaf and Hard-of-Hearing Children: A Systematic Review - and Jarollahi, Farnoush; Fallahnezhad, Tayyebe; Aslibeigi, Farideh (Journal of Modern Rehabilitation, 2025)
Introduction: To systematically review and evaluate the evidence regarding the effect of sign language on language development in deaf and hard-of-hearing children. Materials and Methods: A comprehensive search of electronic databases, including PubMed/ MEDLINE, Web of Science, Scopus, EMBASE, Google Scholar, and ProQuest, from 1995 to April 2024, with no language restrictions, was conducted. Two authors independently assessed the risk of bias using the Newcastle-Ottawa scale (NOS). Results: Six studies involving 259 participants found that exposure to sign language benefits language development in deaf children using hearing aids or cochlear implants (CIs). Children exposed to sign language showed similar or even better spoken language skills than those with limited exposure to sign language. Encouraging parents to learn sign language can significantly support deaf children’s communication and language development. Conclusion: Deaf children with CIs benefit most from communication approaches tailored to their needs. Early intervention, parental involvement, and a rich language environment (signed or spoken) are crucial. While sign language exposure shows promise, further research is needed, especially on its long-term effects and use by hearing parents.
Keywords: Björn-2026-02-22